A Content Review of National Dementia Plans: Are Human Rights Considered? - Briony Harden; Yinuo Mao; Justin Weiss; Selina Hsuan; Orii McDermott; Michelle Funk; Natalie Drew; Katrin Seeher; Tarun Dua; Martin Orrell (Health and Human Rights)
The World Health Organization has set a target for 75% of member states to have national dementia plans by 2025. These plans should align with human rights standards, such as the Convention on the Rights of Persons with Disabilities. The aim of this study was to complete a review of global national dementia plans and their human rights content according to the convention’s principles. A categorization matrix of preidentified human rights themes was produced prior to data collection and extensive inclusion criteria were adopted to ensure thorough assessment using deductive content analysis. Each dementia plan was reviewed by at least two independent assessors. Forty plans were included in the final analysis. We found that basic human rights were covered by the plans, with community inclusion acknowledged in 39 plans (97.5%). However, there was less coverage of non-coercive practices and the participation of people with dementia in the design and delivery of services or policies, with only 24 plans (60%) mentioning these aspects. This is the first global review of human rights content within national dementia plans. More must be done to ensure that all such plans align with human rights standards so that the human rights of persons with dementia are respected, protected, and promoted.